THE BENEFITS OF INTEGRATING VIDEO MAKING IN A SPEAKING CLASS - Riyanto, Edi Dwi (Universitas Ahmad Dahlan, 2020)
Integrated teaching has been advocated and implemented for decades. Lately it has been accelerated by the development of video making. This study aims to investigate the benefits of integrating video making in a speaking class of the 29 first semester students of a public university in Surabaya, East Java Province, Indonesia. It employed action research which was done to improve the quality of the teaching and learning process of the class. The data were collected through direct observation in the classroom, video reviews, and survey. The findings showed that the integration of video making in a speaking class gave benefits to students in the form of four components i.e. social, language and literary, psychological, and technical. The class has been successful in integrating the video making in a speaking class which means that the integration may be applied again in the same class in the future or for a wider scope with similar conditions or settings.